2021
DOI: 10.3390/nu13051432
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Moderate-to-Weak Mediterranean Diet Adherence and Low Scoring for Plant-Based Foods across Several Southern European Countries: Are We Overlooking the Mediterranean Diet Recommendations?

Abstract: The Mediterranean diet (MD) has been sponsored worldwide as a healthy and sustainable diet. Our aim was to update and compare MD adherence and food choices across several Southern European countries: Spain (SP), Portugal (PT), Italy (IT), Greece (GR), and Cyprus (CY) (MED, Mediterranean), and Bulgaria (BG) and the Republic of North Macedonia (NMK) (non-MED, non-Mediterranean). Participants (N = 3145, ≥18 y) completed a survey (MeDiWeB) with sociodemographic, anthropometric, and food questions (14-item Mediterr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 88 publications
0
31
0
Order By: Relevance
“…Unfortunately, many Mediterranean societies are moving away from their traditional dietary pattern, while some countries in Northern Europe and around the world are adopting a Mediterranean-like dietary pattern [25]. For example, previous studies have indicated a persistent moderate-to-weak adherence to the MD across several southern European countries, including Spain, Portugal, Italy, Greece, and Cyprus [58]. Some variations can be expected, probably due to the applied methodological framework and different instru-ments used for assessing adherence to the MD [55].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, many Mediterranean societies are moving away from their traditional dietary pattern, while some countries in Northern Europe and around the world are adopting a Mediterranean-like dietary pattern [25]. For example, previous studies have indicated a persistent moderate-to-weak adherence to the MD across several southern European countries, including Spain, Portugal, Italy, Greece, and Cyprus [58]. Some variations can be expected, probably due to the applied methodological framework and different instru-ments used for assessing adherence to the MD [55].…”
Section: Discussionmentioning
confidence: 99%
“…The current study is part of a research project carried out under the frame of MeDiWeB (Mediterranean Diet and Well-Being) consortium [29][30][31] which was designed to assess MD adherence and other Mediterranean lifestyle characteristics across participants of three MED (Spain, SP; Italy IT; Portugal PT) and two non-MED countries (Bulgaria, BG; Republic of North Macedonia, NMK), and to explore their association with SWB. For this purpose, we developed and applied an online questionnaire (MeDiWeB questionnaire) with 57 questions divided into three sections [29].…”
Section: Study Design and Ethicsmentioning
confidence: 99%
“…After consenting to fill the questionnaire, the participants proceeded to the second section which included a number of questions about sociodemographic characteristics, lifestyle habits, health related characteristics (BMI and diagnosed pathology), and SWB. The third section was devoted to dietary habits and included, among others, the 14 items used to calculate MD adherence (14-MEDAS score) [31]. The questions were structured following the OECD recommendations regarding subjective self-reporting, specifically, inclusion of subjective evaluation questions at or near the beginning of the survey, to avoid any potential bias effects [3].…”
Section: Study Design and Ethicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our interest in food plants was additionally shaped by household food consumption analyses before and shortly after the democratization of the country in 1989, which showed very low consumption of fruits and vegetables. These habits have not changed since then [41,42]. The current paper aimed to provide evidence about food, medicinal and fodder plants grown in home gardens in rural regions in Bulgaria and to discuss the importance of ethnobotanical and horticultural knowledge that backs up the provisional as well as conservational role of these gardens.…”
Section: Introductionmentioning
confidence: 99%